Genome variability of some Gentiana L. species in nature and in culture in vitro: RAPD-analysis - Twardovska, M.O.; Drobyk, N.M.; Mel'nyk, V.M.; Konvalyuk, I.I.; Kunakh, V.A. (Вiopolymers and Cell, 2010)
Aim. Investigation of intraspecies and somaclonal variability of G. acaulis, G. cruciata and G. punctata. Methods. Random amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR), gel-electrophoresis. Results. It was established a species specificity for indicators of gentians genetic heterogeneity – the proportion of polymorphic amplicons and genetic distances. A level of intraspecies variation decreased in the direction of G. acaulis > G. punctata > G. cruciata. Changes in gentians tissue culture by the proportion of polymorphic amplicons were shown to vary within the range of 10–15 % and failed to extend beyond the intraspecies variation. Conclusions. Genome variation of G. acaulis, G. cruciata and G. punctata was studied through the use of RAPD-PCR. The gentians were found to be characterized by different variability in both nature and culture in vitro. In the tissue culture there were discovered considerably smaller number changes as compared to intraspecies variation. Мета. Дослідити внутрішньовидову та сомаклональну мінливість Gentiana acaulis, G. cruciata та G. punctata. Методи. Полімеразна ланцюгова реакція з праймерами довільної послідовності (RAPD- ПЛР), гель-електрофорез. Результати. Виявлено видоспецифічність показників генетичної гетерогенності тирличів – відсотка поліморфних ампліконів і генетичних відстаней. Рівень внутрішньовидової мінливості зменшується у напрямку G. acaulis > G. punctata > G. cruciata. Показано, що зміни в культурі тканин тирличів за вмістом поліморфних ампліконів лежать у діапазоні 10– 15 % і не виходять за межі внутрішньовидової варіабельності. Висновки. Методом RAPD-ПЛР досліджено геномну мінливість G. acaulis, G. cruciata та G. punctata. Встановлено, що тирличі характеризуються різною варіабельністю як у природі, так і в культурі in vitro. У культурі тканин виявлено зміни, які значно менші порівняно з внутрішньовидовою мінливістю. Цель. Исследовать внутривидовую и сомаклональную изменчивость Gentiana acaulis, G. cruciata и G. punctata. Методы. Полимеразная цепная реакция с праймерами произвольной последовательности (RAPD-ПЦР), гель-электрофорез. Результаты. Обнаружена видоспецифичность показателей генетической гетерогенности горечавок – процента полиморфных ампликонов и генетических расстояний. Уровень внутривидовой изменчивости уменьшается в ряду G. acaulis > G. punctata > G. cruciata. Показано, что изменения в культуре тканей горечавок по содержанию полиморфных ампликонов лежат в диапазоне 10– 15 % и не выходят за границы внутривидовой вариабельности. Выводы. Методом RAPD-ПЦР исследована геномная изменчивость G. acaulis, G. cruciata и G. punctata. Установлено, что горечавки характеризуются различной вариабельностью как в природе, так и в культуре in vitro. В культуре тканей обнаружены значительно меньшие изменения по сравнению с внутривидовой изменчивостью.